2017
DOI: 10.1111/ecin.12538
|View full text |Cite
|
Sign up to set email alerts
|

Financial Crises, Output Losses, and the Role of Structural Reforms

Abstract: Financial crises take a heavy toll on output growth. We assess the role of structural reforms in reducing the output losses resulting from financial crises across advanced economies, emerging and developing economies, and low‐income developing economies. We also revisit the role of macroeconomic policies in this context. The impact of crises on output growth differs between types of crises and economies, thus warranting sample splits along these lines. Some but not all reforms and policies help to reduce the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Procyclical lending means that there will be excessive credit in boom times, which has a very high probability of ending in financial crises and economic recessions (Aikman et al, 2015; Baron & Xiong, 2017; Dell’Ariccia et al, 2016; Gorton & Ordoñez, 2019; Jordà et al, 2011; Jordà et al, 2013; Schularick & Taylor, 2012). A financial crisis not only temporarily lowers output but also, and more importantly, permanently damages productivity and growth potential (Cerra & Saxena, 2008; Furceri & Mourougane, 2012; Huber, 2018; Queralto, 2020; Reinhart & Rogoff, 2014; Tola & Waelti, 2018).…”
Section: Challenges Faced By the Literaturementioning
confidence: 99%
“…Procyclical lending means that there will be excessive credit in boom times, which has a very high probability of ending in financial crises and economic recessions (Aikman et al, 2015; Baron & Xiong, 2017; Dell’Ariccia et al, 2016; Gorton & Ordoñez, 2019; Jordà et al, 2011; Jordà et al, 2013; Schularick & Taylor, 2012). A financial crisis not only temporarily lowers output but also, and more importantly, permanently damages productivity and growth potential (Cerra & Saxena, 2008; Furceri & Mourougane, 2012; Huber, 2018; Queralto, 2020; Reinhart & Rogoff, 2014; Tola & Waelti, 2018).…”
Section: Challenges Faced By the Literaturementioning
confidence: 99%
“…Assessing the output losses and the corresponding policies in advanced, developing and lower income countries, Tola & Waelti (2018) suggested that the crises' impact varies for different economies and not all policy measures are effective to cover the output losses from turmoil. The global financial crisis of 2008 caused a more severe recession in the advanced economies as compared to the emerging ones.…”
Section: Literature Reviewmentioning
confidence: 99%